Authentic First Impressions Relate to Interpersonal, Social, and Entrepreneurial Success. Issue 2 (March 2023) - Markowitz, David M.; Kouchaki, Maryam; Gino, Francesca; Hancock, Jeffrey T.; Boyd, Ryan L.
This article examines how verbal authenticity influences person perception. Our work combines human judgments and natural language processing to suggest verbal authenticity is a positive predictor of interpersonal interest (Study 1: 294 dyadic conversations), engagement with speeches (Study 2: 2, 655 TED talks), entrepreneurial success (Study 3: 478 Shark Tank pitches), and social media engagements (Studies 4a–c; N = 387, 039 Tweets). We find that communicating authenticity is associated with increased interest in and perceived connection to another person, more comments and views for TED talks, receiving a financial investment from investors, and more social media likes and retweets. Our work is among the first to evaluate how authenticity relates to person perception and manifests naturally using verbal data.